A novel sensor based on graphene oxide nanoparticles for the detection and analysis of an antihistamine drug. (2019) - Yaragatti, Rubina M.; Malode, Shweta J.; Shetti, Nagaraj P.; Nayak, Deepti S.; Kulkarni, Raviraj M.; Halbhavi, Sadashiv B.; Dandin, Akshata F.; Idli, Deepa C.; S.Kalmani, Sneha; Randewadi, Veeraj A.
Abstract: Graphene oxide adapted carbon paste sensor was developed to study behavior of an antihistamine drug, cetirizine electrochemically. The modified sensor showed enhanced properties and superior sensitivity for cetirizine determination followed by characterization with atomic force microscope. Various voltammetric techniques were used for the quantitative determination of cetirizine and the same were applied for analysis of cetirizine in pharmaceutical and biological fluid samples. A linear response was obtained in the calibration curve for various cetirizine concentrations in the range 0.01-0.4 µM with the detection limit of 1.91 nM. The voltammetric dependence on current, potential, pH, scan rate, concentrations, and excipients was investigated using pH 6.0 phosphate buffer solution. Modification of carbon paste electrode with graphene oxide particles showed good reproducibility, accuracy and time-saving in the analysis.